The effects of motivational approaches on learning interest among sixth from students in Kuching and Samarahan Divisions, Sarawak - Lim, Ivor Emmanuel Ho Huat (1998)
The main purpose of this study was to determine to what extent certain motivational approaches were practiced in the classroom and whether these approaches were related to student interest in learning. It has been argued that the lack of learner-centred motivational strategies have obstructed students from having a keen interest in the learning process. The study made use of the causal-comparative approach to study the main independent variable, motivational approaches, in retrospect for their possible effects to the dependent variable, interest in learning.